PENERAPAN TEKNOLOGI AUGMENTED REALITY PADA APLIKASI MEDIA PEMBELAJARAN MIKROKONTROLER BERBASIS ANDROID DENGAN PLATFORM ARCORE - Irkham Huda; Yusron Fuadi (LPPM STMIK El Rahma Yogyakarta, 2019)
Augmented Reality (AR) is an interactive technology that combines the real and digital world in two-dimensional and three-dimensional forms and projected in a real environment at the same time. Attractive and effective learning media is needed to improve students’s understanding of material, especially if the material requires access to physical objects such as microcontroller learning. By utilizing AR technology, physical objects can be replaced with interactive three-dimensional models. The Mobile based AR application that has been developed in this study as microcontroller learning media was built using the latest AR platform from Google ARCore, that utilizes smartphone cameras to detect flat surfaces, then the selected three-dimensional microcontroller models will appear on the surface without the need to use markers. The developed AR application also has an interactivity feature between users and a three-dimensional model, by generating information of the user selected microcontroller components.